Decision styles and their association with heuristic cue and decision-making rules - Smriti Pathak; Kailash BL Srivastava; Roshan Lal Dewangan (Cogent Psychology, 2023)
AbstractThis study attempts to assess preferences for processing information (decision style) in normative and descriptive decision-making tasks. This study examines the relationship of rational and experiential decision styles with heuristics and the application of decision rules. 324 undergraduate and postgraduate students were drawn purposively from a technical institute. They were administered “Rational‐Experiential Inventory”, “Applying Decision Rule” task and two versions (expert and not-expert) of an essay (as a measure of heuristics). The data were analyzed using descriptive statistics, correlation, and regression techniques. The results suggest that rational decision style (RDS) is positively related to the application of decision rules, but negatively associated with the heuristic cue. Experiential decision style (EDS) and the use of heuristic in decision-making has a significant positive relationship. The application of decision rules (integration skill) and the use of heuristics showed a significant negative correlation. The regression result indicates that both decision styles, rational and experiential, play a significant role in decision-making and impact the use of heuristics and the application of decision rules in decision-making. The findings show the utility of investigating cognitive process manifestations such as decision-making styles and the application of decision-making rules based on competencies.